2017
DOI: 10.5152/eurjrheum.2017.17046
|View full text |Cite
|
Sign up to set email alerts
|

The real-world use of different anti-tumor necrosis factor agents in a Northern European population of patients with Behçet’s disease

Abstract: Objective: The aim of this study was to evaluate prescription practices, treatment responses, and serious adverse events of anti-tumor necrosis factor (anti-TNF) therapies in Behçet's disease (BD). Material and Methods: Patients with BD satisfying the International Study Group for Behçet's Disease or the International Criteria for Behçet's Disease criteria were recruited from a regional rheumatology program. The choice of anti-TNF, treatment response, and adverse events were specified. Response to treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…One possible reason for the increased inflammatory attacks at year 4 might be due to a loss of efficacy and a secondary failure caused by the induction of an anti-IFX antibody. A previous study reported finding that an anti-IFX antibody was produced at 2 years after the administration of IFX in European BS patients 25 . Therefore, these differences between our study and the previous study could potentially be explained by a delay in the production of anti-IFX antibody in the Japanese BS patients as compared to that found in the European population.…”
Section: Discussionmentioning
confidence: 93%
“…One possible reason for the increased inflammatory attacks at year 4 might be due to a loss of efficacy and a secondary failure caused by the induction of an anti-IFX antibody. A previous study reported finding that an anti-IFX antibody was produced at 2 years after the administration of IFX in European BS patients 25 . Therefore, these differences between our study and the previous study could potentially be explained by a delay in the production of anti-IFX antibody in the Japanese BS patients as compared to that found in the European population.…”
Section: Discussionmentioning
confidence: 93%
“…In the study, we found high rates of remission and complete remission in patients with ophthalmic activity. Various studies have also shown significant improvement with IFX and ADA treatments in patients with uveitis and Behçet's disease [2,5,[13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study found high remission rates for oral and skin lesions at 6-month follow-up. Adeeb et al [ 15 ] also found anti-TNF highly effective against mucocutaneous oral and laryngeal manifestations. Moreover, for less common Behçet’s symptoms, such as arthritis, central nervous system (CNS) parenchymal involvement, and vascular lesions, 80.0–100% of patients had remission at 6 or 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in 2017 showed that the use of anti-TNF-α leads to the induction of clinical responses in 100% of the patients and absolute remission in 78% of the patients. These biological agents can be used as an alternative treatment option in BD patients, who have failed to respond to formal immunosuppressive treatments (Adeeb et al, 2017). Additionally, TNF-α inhibitor therapy prevents T-cell differentiation in BD patients, who suffer from uveitis (Sugita et al, 2012).…”
Section: Tumor Necrosis Factor α (Tnf-α)mentioning
confidence: 99%